Integration of single-atom catalyst with Z-scheme heterojunction for cascade charge transfer enabling highly efficient piezo-photocatalysis - Jiang, Wenbin (2023)
Piezo-assisted photocatalysis (namely, piezo-photocatalysis), which utilizes mechanical energy to modulate spatial and energy distribution of photogenerated charge carriers, presents a promising strategy for molecule activation and reactive oxygen species (ROS) generation toward applications such as environmental remediation. However, similarly to photocatalysis, piezo-photocatalysis also suffers from inferior charge separation and utilization efficiency. Herein, a Z-scheme heterojunction composed of single Ag atoms-anchored polymeric carbon nitride (Ag-PCN) and SnO2- x is developed for efficient charge carrier transfer/separation both within the catalyst and between the catalyst and surface oxygen molecules (O2 ). As revealed by charge dynamics analysis and theoretical simulations, the synergy between the single Ag atoms and the Z-scheme heterojunction initiates a cascade electron transfer from SnO2- x to Ag-PCN and then to O2 adsorbed on Ag. With ultrasound irradiation, the polarization field generated within the piezoelectric hybrid further accelerates charge transfer and regulates the O2 activation pathway. As a result, the Ag-PCN/SnO2- x catalyst efficiently activates O2 into ·O2 - , ·OH, and H2 O2 under co-excitation of visible light and ultrasound, which are consequently utilized to trigger aerobic degradation of refractory antibiotic pollutants. This work provides a promising strategy to maneuver charge transfer dynamics for efficient piezo-photocatalysis by integrating single-atom catalysts (SACs) with Z-scheme heterojunction.